2013
DOI: 10.1021/am404031q
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a New Hydrous Zr(IV) Oxide-Based Nanocomposite for Enhanced Pb(II) and Cd(II) Removal from Waters

Abstract: To overcome the technical bottleneck of fine hydrated Zr(IV) oxide particles in environmental remediation, we irreversibly impregnated nanosized hydrated Zr(IV) oxide inside a commercial cation exchange resin D-001 and obtained a new nanocomposite NZP. NZP exhibited efficient removal of lead and cadmium ions in a pH range of 2-6, where no Zr(IV) leaching was detected from NZP. As compared to D-001, NZP showed more preferable adsorption toward both toxic metals from the background Ca(II) solution at greater lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(43 citation statements)
references
References 40 publications
2
41
0
Order By: Relevance
“…It is particularly significant to test the effect of coexisting ions because they are commonly present in natural waters . Here, we investigated the effect of varied coexisting ions with different concentrations on the absorbed amount of Cd II by γ‐CD MOF‐NPC.…”
Section: Resultsmentioning
confidence: 99%
“…It is particularly significant to test the effect of coexisting ions because they are commonly present in natural waters . Here, we investigated the effect of varied coexisting ions with different concentrations on the absorbed amount of Cd II by γ‐CD MOF‐NPC.…”
Section: Resultsmentioning
confidence: 99%
“…NPs could pose some intrinsic potential risks. For example, the biocompatibility investigations of graphene and graphene oxide have been unsatisfactory with some papers demonstrating severe dose-dependent toxicity (Hu et al, 2011;Wang et al, 2011), while others indicated that graphene NPs might improve cell growth (Lee et al, 2011;Ruiz et al, 2011). Furthermore, not only the environmental toxicity, but also the fate of NPs remains poorly understood, even for the most toxic NPs like Ag.…”
Section: Toxicity Evaluationmentioning
confidence: 99%
“…Recently, Hua et al impregnated nano‐sized hydrated Zr(IV) oxide inside a commercial cation exchange resin, D001, and obtained a new nanocomposite with efficient removal of Pb(II) and Cd(II) ions in the pH range 2–6 without leaching of nanoparticles. Regarding the mechanism, the adsorbent exhibited non‐specific ion exchange by the sulfonate groups of D001 and specific inner‐sphere complexation by the entrapped hydrous zirconium oxide (HZO) nanoparticles …”
Section: Polymer Nanocomposites and Hybridsmentioning
confidence: 99%
“…Regarding the mechanism, the adsorbent exhibited non-specific ion exchange by the sulfonate groups of D001 and specific inner-sphere complexation by the entrapped hydrous zirconium oxide (HZO) nanoparticles. 128 Ferric-oxide-loaded glycidylmethacrylate-based polymers were investigated for the removal of Cr(VI) from aqueous solution. The adsorbents showed good adsorption capacity for Cr(VI) ions and good chemical stability in a wide pH range because the crosslinked polymers have advantages over other polymer supports due to ease of functionalization through the epoxide groups involved and resistance of their ester linkage to acid and to base hydrolysis.…”
Section: Polymer Nanocomposites and Hybridsmentioning
confidence: 99%